2016
DOI: 10.1021/acs.jpcc.6b00925
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Hopping Transport in Molecular Wires 4 nm in Length

Abstract: We report the synthesis and electrical characterization of photoswitchable π-conjugated molecular wires. The wires were designed based on the previously reported oligophenyl­eneimine (OPI) wires [ Frisbie Frisbie Science20083201482] with a slight modification to incorporate the dithienylethene linker (the “photoswitch”) into the wire backbone (e.g., PS3-OPI 5; PS stands for the photoswitch, and the number following “PS’’ indicates its position within the OPI chain). Stepwise arylimine condensation reaction be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…[1] Ak ey aspect of molecular electronics from the perspective of chemists is,however, the possibility of exploring alarge chemical space to i) tune the device response to the desired range and magnitude,o btaining, in turn, important insights on structure-property relationships,a nd ii)study phenomena unique to the molecular and quantum world. Since the first pioneering studies in the late 1990s, [2] singlemolecule devices with behaviour like semiconductor-based diodes, [3,4] resistors, [5] switches, [6][7][8][9] and transistors [10][11][12][13] have been demonstrated, and the chemical complexity of the molecules used to fabricate junctions has rapidly increased. Stemming from the original studies employing simple aliphatic and conjugated rod-like oligoaryl moieties, [14] it is now common to read reports on molecular wires incorporating fused polyaromatic/heterocyclic systems, [15,16] supramolecular complexes, [17,18] organometallic centres, [19,20] and, more recently,p olynuclear clusters.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Ak ey aspect of molecular electronics from the perspective of chemists is,however, the possibility of exploring alarge chemical space to i) tune the device response to the desired range and magnitude,o btaining, in turn, important insights on structure-property relationships,a nd ii)study phenomena unique to the molecular and quantum world. Since the first pioneering studies in the late 1990s, [2] singlemolecule devices with behaviour like semiconductor-based diodes, [3,4] resistors, [5] switches, [6][7][8][9] and transistors [10][11][12][13] have been demonstrated, and the chemical complexity of the molecules used to fabricate junctions has rapidly increased. Stemming from the original studies employing simple aliphatic and conjugated rod-like oligoaryl moieties, [14] it is now common to read reports on molecular wires incorporating fused polyaromatic/heterocyclic systems, [15,16] supramolecular complexes, [17,18] organometallic centres, [19,20] and, more recently,p olynuclear clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular switches, among other single molecule electronic units, are characterized as bi-stable systems in which reversible switching of various physical and chemical properties is achieved through exposure to external stimulus. The two forms of the switching molecule may differ by numerous attributes such as cis-trans isomerism [21][22][23][24] , chirality 25 , open-closed ring structure, [26][27][28] or tautomeric structure [29][30][31][32][33] . Up to date, the palette of experimentally studied factors allowing for the switching control includes an external electromagnetic irradiation 21,26,34 , electric current transmission 29,35 , static electric 22 and magnetic 26 fields, short-range forces 36 , temperature 26,37 , chemical reactions, 38,39 and mechanical stretching 40 .…”
Section: Introductionmentioning
confidence: 99%
“…The DCP unit undergoes a photocyclization reaction from the open to the closed form upon irradiation with light in the UV spectral range (280 nm–350 nm) and a photocycloreversion reaction upon irradiation with light in the visible spectral range (450 nm–650 nm). In recent work, it has been demonstrated that it is possible to modulate the electrical and/or optical properties of molecular dyads, organic transistors, molecular wires, or nanoparticle networks as a function of the light-induced alteration of the state of the DCP 20 21 22 23 24 25 .…”
mentioning
confidence: 99%